2016
DOI: 10.3389/fpsyg.2016.01911
|View full text |Cite
|
Sign up to set email alerts
|

Through the Looking Glass: The Role of Ethnicity and Affiliation in Responses to Terrorism in the Media

Abstract: This study examined whether attitudinal and emotional responses to broadcasts of images of terrorist events differ according to ethnic group (Jewish and Arab Israelis) and outgroup affiliation during an intense wave of terrorism that occurred in Israel during 2015. Participants were 118 Jewish and 110 Arab-Israelis adults randomly allocated to a terrorism or criminal violence television broadcast. State anxiety, state anger, stereotypes, and negative attitudes toward an adversary were examined prior and subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…At a 2 Recently, studies have started to unravel moderators affecting to what extent terrorism affects attitudes. Individual-level moderators include citizens' gender (Lindner 2018;Lizotte 2017), ethnicity (Lavi et al 2014;Shoshani andSlone 2016), educational level (Ferrín, Mancosu, andCappiali 2020), political predispositions (Castanho Silva 2018; Castano et al 2011;Hetherington and Suhay 2011;Nail et al 2009;Van de Vyver et al 2016), political knowledge (Carriere, Hendricks, and Moghaddam 2019), ingroup attachment (Asbrock and Fritsche 2013;Bilali 2015), and motivation to control prejudice (Jacobs and van Spanje 2021;Sobolewska, Ford, and Sniderman 2017;Steen-Johnsen and Winsvold 2020).Countryand context-level moderators include unemployment rates (Castanho Silva 2018; Legewie 2013), the local migration context (Castanho Silva 2018; Nussio, Bove, and Steele 2019), geographical proximity (Finseraas and Listhaug 2013;Nussio, Bove, and Steele 2019), political-ideological climate (Ferrín, Mancosu, and Cappiali 2020), and prevailing social norms (Álvarez-Benjumea and Winter 2020).Terrorism-specific moderators include the terrorist's gender (Lindner 2018), ideology (Jacobs and van Spanje 2021;Piazza 2015), and the way terrorism is communicated and framed (Bruneau, Kteily, and Urbiola 2020;Canetti et al 2018;Gadarian 2010;von Sikorski et al 2017). 3 The main datafile in the Replication Materials lists all theories on which the manuscripts included in this meta-analysis draw (see https://doi.org/10.7910/DVN/K4L5YI).…”
Section: How and Why Terrorism Affects Attitudesmentioning
confidence: 99%
“…At a 2 Recently, studies have started to unravel moderators affecting to what extent terrorism affects attitudes. Individual-level moderators include citizens' gender (Lindner 2018;Lizotte 2017), ethnicity (Lavi et al 2014;Shoshani andSlone 2016), educational level (Ferrín, Mancosu, andCappiali 2020), political predispositions (Castanho Silva 2018; Castano et al 2011;Hetherington and Suhay 2011;Nail et al 2009;Van de Vyver et al 2016), political knowledge (Carriere, Hendricks, and Moghaddam 2019), ingroup attachment (Asbrock and Fritsche 2013;Bilali 2015), and motivation to control prejudice (Jacobs and van Spanje 2021;Sobolewska, Ford, and Sniderman 2017;Steen-Johnsen and Winsvold 2020).Countryand context-level moderators include unemployment rates (Castanho Silva 2018; Legewie 2013), the local migration context (Castanho Silva 2018; Nussio, Bove, and Steele 2019), geographical proximity (Finseraas and Listhaug 2013;Nussio, Bove, and Steele 2019), political-ideological climate (Ferrín, Mancosu, and Cappiali 2020), and prevailing social norms (Álvarez-Benjumea and Winter 2020).Terrorism-specific moderators include the terrorist's gender (Lindner 2018), ideology (Jacobs and van Spanje 2021;Piazza 2015), and the way terrorism is communicated and framed (Bruneau, Kteily, and Urbiola 2020;Canetti et al 2018;Gadarian 2010;von Sikorski et al 2017). 3 The main datafile in the Replication Materials lists all theories on which the manuscripts included in this meta-analysis draw (see https://doi.org/10.7910/DVN/K4L5YI).…”
Section: How and Why Terrorism Affects Attitudesmentioning
confidence: 99%
“…A meta-analysis showed that a sense of discrimination predicts intergroup violent attitudes, and a greater sense of injustice increases the willingness to commit IV (Wolfowicz et al, 2020). While research has focused on one type of microaggression—stereotypes toward other ethnic groups, including Jews toward Arabs in Israel and vice versa (Shoshani & Slone, 2016)—microaggression has not been tested so far, as a risk factor for IV (Wolfowicz et al, 2020).…”
Section: The Israeli Contextmentioning
confidence: 99%
“…In addition, the increasing incidence of war, armed conflict, and terrorism has become a global problem, reaching deep into societies and communities, targeting civilians and inducing mass anxiety, fear, a continuous sense of threat, and helplessness [ 9 , 10 , 11 ]. Millions of children and adolescents are indirectly exposed to war, armed conflict, and terrorism through the media, with adverse effects [ 12 , 13 , 14 , 15 ]. The use of smartphones and computers in the hands of the youth may be portals to extremely dangerous places.…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of uploading and publishing any information, with no need for monitoring or approval from authorities, is an immense advantage [ 14 , 16 , 41 , 42 ]. Moreover, social media platforms such as Facebook, Twitter, Instagram, or Tik-Tok enable the creation of social networks [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation